Collaborative Business Model Innovation: A Case Study of Indonesia's Muslim Fashion Creative Economy Ecosystem - Mazidah, Nurul; Hidayat, Muhammad Syahrul; Hamid, Ahmad Munir (Indonesian Journal for Entrepreneurial Review, 2025)
The creative economy sector in Indonesia, particularly the Muslim fashion industry, has shown significant potential for growth and innovation through the adoption of collaborative business models. This research aims to explore and analyze collaborative business model innovations in the Muslim fashion creative economy ecosystem in Indonesia, focusing on the factors that support its success as well as the challenges faced. Entrepreneurial ecosystems involving governments, higher education institutions, and professional infrastructure play an important role in driving digitalization and innovation among MSMEs, which in turn promotes sustainability. A business incubation model involving mentors and a structured curriculum has proven effective in enhancing product innovation and marketing among creative entrepreneurs. A case study in Bandung, known for its vibrant creative economy, shows how collaborative governance involving multiple stakeholders can drive economic growth and competitiveness. The results of this study also discover the importance of blue ocean strategies and collaborative economies, which emphasize sharing resources and knowledge, as well as the integration of digital platforms that combine market models and crowdfunding, to increase market access and meet consumer needs.